Association Between Screw-Press Operating Pressure And Oil Loss In Press Fibre At PTPN IV Kebun Mayang Palm Oil Milll - Kevin Rolinson Manullang; Daniel Tony Edyt Siburian (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Screw-press operation is a major determinant of oil recovery at the pressing station of a palm oil mill, but field comparisons may be distorted when pressure levels are observed on different machines. This study re-examined the relationship between operating pressure and residual oil in press fibre at PTPN IV Kebun Mayang using an observational dataset comprising 15 once-daily measurements from three screw presses over five recorded sampling dates in 2025. Operating pressure was recorded at the time of sampling, and press-fibre oil, moisture, and non-oil solids were measured on a wet basis using a FOSS NIRS DA1650 instrument with the installed mill calibration. Mean pressure and oil loss were 40.4 ± 1.82 bar and 3.756 ± 0.804% for Machine 1, 45.0 ± 4.00 bar and 3.404 ± 0.476% for Machine 2, and 50.0 ± 1.58 bar and 3.176 ± 0.423% for Machine 3. An unadjusted linear regression indicated a decrease of 0.088 percentage points in oil loss per 1-bar increase in observed pressure (95% CI: −0.142 to −0.034; p = 0.004). After adjustment for machine and sampling date, the estimated pressure coefficient was smaller and statistically uncertain (−0.039 percentage points per bar; 95% CI: −0.164 to 0.086; p = 0.485). The data therefore suggest an inverse descriptive relationship between pressure and oil loss, but they do not establish a causal pressure effect or identify an optimum pressure because pressure was confounded with machine identity and kernel damage, oil impurities, energy consumption, throughput, and equipment wear were not quantified.